Hearing Profile of Children Below Three Years Old at Jatinangor Integrative Health Care Center, West Java, Indonesia - Fidkya Allisha; Wijana Wijana; Sally Mahdiani (Althea Medical Journal, 2022)
Background: Hearing function is one of the most important factors affecting children’s development process. The first three years of life is a golden period of growth and development of children. This study was conducted to investigate the hearing profile of children below three years old at Jatinangor Integrative Health Care Center (Pos Pelayanan Terpadu, Posyandu), West Java, Indonesia.Methods: An observational cross-sectional study was conducted to 86 children below three years old who was selected by using multistage cluster sampling at 12 Posyandu in Jatinangor sub-district by using in-depth interview related to hearing loss risk factors, reaction test, and tympanometry test.Results: The hearing loss prevalence of children below three years old in the Jatinangor sub-district was 7.0%. Of the 86 children, there were 2.3% (n=2) children with moderate conductive hearing loss, 1.2% (n=1) children with moderate sensorineural hearing loss, and 3.5% (n=3) children with very severe sensorineural hearing loss. Fifty percent of children with sensorineural hearing loss were discovered without any risk factor.Conclusions: The prevalence of hearing loss in children under three years old at the Jatinangor Integrative Health Care Center is slightly higher than the national prevalence. Fifty percent of children are found without risk factors, therefore Universal Newborn Hearing Examination (UNHS) needs to be implemented at the national level in accordance with the guidelines of the Joint Committee for Infant Hearing (JCIH) in which are integrated with primary health care units, tertiary health care centers otorhinolaryngology, and also the audiological center.